Lo sviluppo nel retail come modalita’ di internazionalizzazione delle pmi manifatturiere. Il caso della moda - Guercini, Simone; Runfola, Andrea (Piccola Impresa / Small Business, 2016)
This article examines the process of internationalization through retail stores of the SMEs fashion manufacturers firms. In particular, the article presents the results of the analysis of a database build ad hoc by the authors on the openings of retail stores by manufacturing firms in the fashion industry in the period 2004-2013. The article analyzes 2,127 openings, highlighting the role of SMEs, which account for a significant percentage of these openings. The results highlight the path of the development in terms of countries involved and some elements of difference between SMEs and large enterprises. The paper ends with some tentative research implications